Ediacaran Extinction and Cambrian Explosion. (September 2018) - Darroch, Simon A.F.; Smith, Emily F.; Laflamme, Marc; Erwin, Douglas H.
Abstract : The Ediacaran–Cambrian (E–C) transition marks the most important geobiological revolution of the past billion years, including the Earth's first crisis of macroscopic eukaryotic life, and its most spectacular evolutionary diversification. Here, we describe competing models for late Ediacaran extinction, summarize evidence for these models, and outline key questions which will drive research on this interval. We argue that the paleontological data suggest two pulses of extinction – one at the White Sea–Nama transition, which ushers in a recognizably metazoan fauna (the 'Wormworld'), and a second pulse at the E–C boundary itself. We argue that this latest Ediacaran fauna has more in common with the Cambrian than the earlier Ediacaran, and thus may represent the earliest phase of the Cambrian Explosion. Highlights: We provide evidence for a two-phased biotic turnover event during the Ediacaran–Cambrian transition (about 550–539 Ma), which both comprises the Earth's first major biotic crisis of macroscopic eukaryotic life (the disappearance of the enigmatic 'Ediacara biota') and immediately precedes the Cambrian explosion. We summarize two competing models for the turnover pulses – an abiotically driven model (catastrophe) analogous to the 'Big 5' Phanerozoic mass extinction events, and a biotically driven model (biotic replacement) suggesting that the evolution of bilaterian metazoans and ecosystem engineering were responsible. We summarize the evidence in support of both models and identify several key research questions which will help to distinguish between them, and thus shed light on the origins of the modern, animal-dominated biosphere. We argue that the first turnover pulse (about 550 Ma) marks the greatest change in organismal and ecological complexity, leading to a more recognizably metazoan global fauna that has much more in common with the Cambrian than the earlier Ediacaran. This latest Ediacaran interval (the 'Nama') may therefore represent the earliest phase of the Cambrian Explosion.